Measuring Constructs of the Consolidated Framework for Implementation Research in the Context of Increasing Colorectal Cancer Screening in Federally Qualified Health Center - Kegler, Michelle C. (Health Serv Res, 2018)
OBJECTIVE: To operationalize constructs from each of the Consolidated Framework for Implementation Research domains and to present psychometric properties within the context of evidence‐based approaches for promoting colorectal cancer screening in federally qualified health centers (FQHCs). METHODS: Data were collected from FQHC clinics across seven states. A web‐based Staff Survey and a Clinic Characteristics Survey were completed by staff and leaders (n = 277) from 59 FQHCs. RESULTS: Internal reliability of scales was adequate ranging from 0.62 for compatibility to 0.88 for other personal attributes (openness). Intraclass correlations for the scales indicated that 2.4 percent to 20.9 percent of the variance in scale scores occurs within clinics. Discriminant validity was adequate at the clinic level, with all correlations less than 0.75. Convergent validity was more difficult to assess given lack of hypothesized associations between factors expected to predict implementation. CONCLUSIONS: Our results move the field forward by describing initial psychometric properties of constructs across CFIR domains.